2018
DOI: 10.3906/biy-1711-26
|View full text |Cite
|
Sign up to set email alerts
|

Increased elastic modulus of plasma polymer coatings reinforced with detonation nanodiamond particles improves osteogenic differentiation of mesenchymal stem cells

Abstract: In the present study we demonstrated that composite PPHMDS/DND coatings with elastic moduli close to those of mature bone tissue (0.2-2.8 GPa) stimulated growth and osteogenic differentiation of human adipose-derived mesenchymal stem cells (hAD-MSCs). Composite coatings were prepared by a method of plasma polymerization (PP) where detonation nanodiamond (DND) particles in different amounts (0.1, 0.5, and 1 mg/mL) were added to hexamethyldisiloxane (HMDS) before plasma deposition. This method allows variation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 55 publications
1
1
0
Order By: Relevance
“…As mentioned above, the microdiamond interlocks the polymer matrix and restricts its mobility, resulting in higher elastic modulus. This significant increase in the elastic modulus is also in agreement with similar previous studies. , The reported elastic moduli of various 3D printable polymers and composites are also given within Table .…”
Section: Results and Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As mentioned above, the microdiamond interlocks the polymer matrix and restricts its mobility, resulting in higher elastic modulus. This significant increase in the elastic modulus is also in agreement with similar previous studies. , The reported elastic moduli of various 3D printable polymers and composites are also given within Table .…”
Section: Results and Discussionsupporting
confidence: 92%
“…These include its hydrophilicity, biocompatibility, nontoxicity, thermal stability, thermal conductivity, electrical insulation (or indeed electrical conductivity in boron-doped variants), hardness, wear resistance, and low cost. Hence, several studies have already reported the advantages of nano- and microdiamonds as reinforcing enhancers in polymer composites. …”
Section: Introductionmentioning
confidence: 99%